2014
DOI: 10.1016/j.mjafi.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro vancomycin susceptibility amongst methicillin resistant Staphylococcus aureus

Abstract: Methods: A prospective study was undertaken at tertiary care hospital; 232 clinical MRSA isolates were included. Vancomycin MIC was undertaken by agar dilution method and E test.Results: All isolates were sensitive to Linezolid. Two MRSA isolates had vancomycin MIC !4 mg/ml; vancomycin MIC50 and MIC90 of MRSA isolates was 0.5 and 0.2 mg/ml respectively by agar dilution method. There was agreement over 93.5% isolates in vancomycin susceptibility by agar dilution and E test. E test had sensitivity and positive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…They isolated 4 VISA with MIC 4 by E test and 2 VISA by agar dilution which is similar to our study. 29 Prakash et al reported 69 (98%) MRSA with MIC 2 for vancomycin by E test which is also near to our study. 30 Havaei et al from Iran isolated 5 (4.34%) VISA by E strip and then subjected to PCR analysis.…”
Section: Vancomycin Mic Among Mrsa By E Stripsupporting
confidence: 89%
See 1 more Smart Citation
“…They isolated 4 VISA with MIC 4 by E test and 2 VISA by agar dilution which is similar to our study. 29 Prakash et al reported 69 (98%) MRSA with MIC 2 for vancomycin by E test which is also near to our study. 30 Havaei et al from Iran isolated 5 (4.34%) VISA by E strip and then subjected to PCR analysis.…”
Section: Vancomycin Mic Among Mrsa By E Stripsupporting
confidence: 89%
“…They concluded that E test was found equally sensitive as compared to agar dilution method in screening MRSA for vancomycin susceptibility. But agar dilution method is time consuming, cumbersome and so E test can be used as an alternative to agar dilution method 29.…”
mentioning
confidence: 99%
“…[18] . While data of a surveillance study of S. aureus isolates from the Europe and USA reported a very low prevalence (<0.3%) of vancomycin intermediates among total S. aureus isolates (>300,000) [16,25] . A recent study from South India indicated a high prevalence of VRSA and VISA among hospitalized patients [12] .…”
Section: Resultsmentioning
confidence: 99%
“…[15] Currently there are many studies support a reduction in vancomycin susceptibility globally, including India. [16,17,18,19] The higher rate of emergence of VRSA has made the antibiotic therapy for S. aureus associated disease a global challenge. [20,12] water bath for 5 min at 95°C followed by phenol/chloroform extraction.…”
Section: Introductionmentioning
confidence: 99%
“…10 The trapped molecules clog the peptidoglycan meshwork and finally form a physical barrier towards further incoming vancomycin molecules. 11 A recent prospective study "In vitro vancomycin susceptibility amongst methicillin resistant S. aureus" by Chaudhari et al 12 at a tertiary care hospital analyzing 232 clinical MRSA isolates, published in this issue, highlights the importance of determination of vancomycin and linezolid minimum inhibitory concentrations (MIC) by agar dilution method and epsilometer (E test). All isolates were found sensitive to linezolid.…”
mentioning
confidence: 99%